HAMBATAN IMPLEMENTASI SISTEM INFORMASI KESEHATAN DAERAH GENERIK DI UNIT PELAKSANA TEKNIS DAERAH PUSKESMAS KABUPATEN JEMBRANA - Dewayanti Kepakisan, Desak Putu Rizka; Nopiyani, Ni Made Sri (ARCHIVE OF COMMUNITY HEALTH; Vol 11 No 3 (2024): Desember 2024DO - 10.24843/ACH.2024.v11.i03.p24, 2025)
The implementation of SIKDA Generic in Jembrana Regency community health care has been implemented since 2017 but cannot be used optimally. This study aims to explore barriers in terms of inputs to the implementation of SIKDA Generic This study used a qualitative descriptive design with an in-depth interview data collection method with 10 informants there are head of the community health care, the chief administrative officer, the person in charge of essential program, the person in charge of individual health, pharmaceuticals and laboratory, the person in charge of the general clinic room, and the staff of community health care. The data analysis technique used was thematic analysis using semi-structured interview guidelines. This research is guided by the Health Metrics Network (HMN) Framework and the result shows that there are barriers to the implementation of SIKDA Generic in terms of input, namely the absence of demands, commitment and implementation roadmap, lack of communication, the absence of specific policies from both the health office and community health care, the absence of budget allocation, the availability of human resources, the quantity and quality of human resources, the availability of training and mentoring, inadequate facilities and infrastructure related to system networks and modules, and the appearance of SIKDA Generic which is not user friendly. The findings of this study suggest that all relevant stakeholders at all levels start implementing efforts to the barriers of the implementation of SIKDA Generic to create a more effective and efficient integrated Indonesian Health Information System. Keywords: Health Information System, Primary Health Care, SIKDA Generic